2019
DOI: 10.3390/fermentation5030067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-Inoculation with Pichia fermentans and Pediococcus acidilactici on Metabolite Produced During Fermentation and Volatile Composition of Coffee Beans

Abstract: Removal of the mucilage layer of coffee fruits by a fermentation process has became an interesting strategy to improve coffee quality, which is able to assist the formation of flavored molecules. In this study, four sets of inoculation protocols were evaluated using ripe and immature coffee fruits, respectively, including (i) pure culture fermentation with Pichia fermentans, (ii) pure culture fermentation with Pediococcus acidilactici, (ii) combined fermentation with P. fermentans and P. acidilactici, and (iv)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 51 publications
0
15
0
2
Order By: Relevance
“…Yeasts such as H. opuntiae have been associated with 2-phenylethyl acetate and ethyl hexanoate production ( Hu et al., 2018 ). Esters are mostly produced by the synergy between yeasts and LAB in the anaerobic stage of fermentation ( da Silva Vale et al., 2019 ; Hamdouche et al., 2019 ). The results of this study could indicate a greater production of esters under the B2 method due to the lower aeration incorporated into cocoa-pulp mass as compared to the B1 method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeasts such as H. opuntiae have been associated with 2-phenylethyl acetate and ethyl hexanoate production ( Hu et al., 2018 ). Esters are mostly produced by the synergy between yeasts and LAB in the anaerobic stage of fermentation ( da Silva Vale et al., 2019 ; Hamdouche et al., 2019 ). The results of this study could indicate a greater production of esters under the B2 method due to the lower aeration incorporated into cocoa-pulp mass as compared to the B1 method.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, P. acidilactici was identified under B1 fermentation, which is a species that shows higher production of ethyl acetate when coinoculated with yeasts of the genus Pichia spp. than when grown in isolation ( da Silva-Vale et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These species have been frequently isolated in spontaneous coffee fermentations performed in Australia, Brazil, Colombia, China, Ecuador, and Tanzania (Masoud et al ., 2004; de Melo Pereira et al ., 2014; Evangelista et al ., 2015; Junqueira et al ., 2019; Zhang et al ., 2019a,b; Pothakos et al ., 2020). Pichia and Hanseniaspora are associated with flavour‐active ester production impacting distinct floral and fruity notes in coffee beverages, while Candida species are known to assist in the process of coffee removing mucilage through the production of pectinolytic enzymes (Masoud et al ., 2005; Masoud and Jespersen, 2006; de Melo Pereira et al ., 2014; da Silva et al ., 2019; Giorello et al ., 2019). In addition to yeasts, filamentous fungi belonging to the Order Tremellales and Fusarium were detected within the core microbiome (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using this strategy, they were able to clearly demonstrate the implication of yeasts in the quality improvement of the wetprocessed coffee. Finally, several authors also demonstrated the improvement of the quality after the inoculation of selected yeasts and lactic acid bacteria strains on coffee undergoing not only the wet (De Melo Pereira et al, 2015b, 2016Da Silva Vale et al, 2019;Bressani et al, 2020) but also the semidry processing (Martinez et al, 2017).…”
Section: Potential Uses As Biocontrol Agentsmentioning
confidence: 97%